The Influence of Employee Discipline, Learning and Supervision on the Service Performance of Public Works in Bina Marga Office of Ponorogo Regency - Noer Soetjipto; Gogi Kurniawan; Sulastri Sulastri; Ari Riswanto (Publindo Akademika, 2021)
This study aims to the influence of employee discipline, learning and supervision on the service performance of public works in Bina Marga office of Ponorogo Regency. The results showed the simultaneous influence of discipline and organizational learning behavior on the performance. The results empirically prove that discipline and organizational learning behavior is highly relevant as a measuring tool with sufficient accuracy to determine the service performance of service employees in the Public Works and Bina Marga Office of Ponorogo Regency. The simultaneous influence of employee discipline with learning behavior of organization on employees in the licensing sector at PU in Ponorogo Regency which has an impact on the performance or performance of public services can be illustrated that Public Works Department employees as a learning organization are not far from the mindset that only senior management can and do all the thinking for the whole institution. The learning behavior of organization challenges all employees to utilize their mental resources and potential, with the hope that every employee in the PU office can build their own community based on the principles of freedom, humanity, and a collective desire to learn. As a managerial implication, it can be said that discipline in the work process at the Ponorogo District Public Works office goes hand in hand with the willingness of employees to increas discipline and organizational learning behavior which are correlated to form service performance